The prospects of burning coal and oil processing waste in slurry, gel, and solid state; Applied Thermal Engineering; Vol. 156 - Vershinina K. Yu. Kseniya Yurievna; Nyashina G. S. Galina Sergeevna; Dorokhov V. V. Vadim Valerjevich; Shlegel N. E. Nikita Evgenjevich (2019, 2019)
Title screen